UPAYA PENINGKATAN KEMAMPUAN KEAKSARAAN DENGAN METODE TEKA-TEKI BERGAMBAR DI RA AR-ROMALIYAH DUSUN SLUMBUNG DESA PADAS TAHUN PELAJARAN 2021/2022 - ucik Binsa; Uswatun Khasanah (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2022)
The picture puzzle method is guessing, guessing and guessing about questions in the form of sentences, stories or pictures that are presented vaguely, usually to sharpen the mind. Literacy is the ability to name known symbols, recognize sounds, the initial letters of the names of objects around, mention groups of pictures that have the same sound or initial letters, write their own names and read their own names. The objectives of this study are: (1) To describe the process of literacy skills in the pictorial puzzle method at RA Ar-Romaliyah, Slumbung hamlet, Padas village.(2) To improve children's writing and reading skills through the picture puzzle method at RA Ar-Romaliyah Dusun Slumbung Padas Village. This type of research uses a qualitative approach with a descriptive method, where data is collected by means of observation, interviews and documentation. The sources of this research are the Principal, Class B homeroom teacher and students. The results of this study will be presented in the form of sentences, not in the form of numbers. The analysis technique that the writer uses is data reduction, data presentation and conclusion drawing. Based on the research that has been done, it shows that: (1) To describe the process of applying literacy skills in the pictorial puzzle method at RA Ar-Romaliyah, Slumbung hamlet, Padas village. (2) To determine the impact of improving children's writing and reading skills through the use of the picture puzzle method at RA Ar-Romaliyah Dusun Slumbung Padas Village. Key Words: Literacy, Picture Puzzle Method